Analysis of the Effectiveness of Using VHF Radio Channel 12 to Assist the Maneuvering Guidance Process on the Km. Binaiya Ship - Risma Yanuar Azizah; Firdaus Sitepu; Dian Junita Arisusanty; I'ie Suwondo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Indonesia's vast maritime domain demands effective VHF radio communication for safe ship maneuvering amid congested routes, as mandated by SOLAS Chapter IV GMDSS for vessels over 300 GT; Channel 12 supports pilotage coordination on KM. Binaiya, yet technical faults, SOP non-compliance, and traffic density hinder efficacy. This qualitative descriptive study aims to analyze influencing factors and impacts, using Purposive Sampling of 5-10 crew (captain, officers, radio operators), semi-structured interviews, observation sheets, SMCP SOP documentation, and Miles-Huberman analysis (reduction, display, verification). Findings reveal technical issues (noise, corrosion, irregular self-tests), inconsistent SMCP SOP (read-back lapses), and high traffic (eg, 7,000–12,000 ships/week in Makassar) cause overlaps; impacts include reduced clarity, coordination delays, increased collision risks. VHF Channel 12 efficacy is suboptimal; recommend routine training, maintenance, VTS oversight. Future research: quantitative SNR analysis